2021
DOI: 10.3389/fmars.2021.763922
|View full text |Cite
|
Sign up to set email alerts
|

Monoculture or Mixed Culture? Relevance of Fine Root Dynamics to Carbon Sequestration Oriented Mangrove Afforestation and Restoration

Abstract: Fine root dynamics have the potential to contribute to ecosystem biogeochemical cycling, especially for carbon. This is particularly true in mangroves which are the most productive and carbon-rich ecosystems of the world. However, few studies comprehensively evaluated the contribution of mangrove fine root dynamics to soil organic carbon accumulation. In southern China, while the introduced fast-growing Sonneratia apetala and native shrubby Kandelia obovata have been widely used in mangrove reforestation/affor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 75 publications
0
5
0
Order By: Relevance
“…Several studies also reported that coastal ecosystems vegetated with different mangrove species showed substantial variations in sediment properties, including pH, salinity, TC, and TN 32,47 . In this study, we observed different nutrient statuses (TC, TN, ammonium, and sulfate) and environmental conditions (pH and salinity) between native and introduced mangrove rhizospheres, which might be influenced by plant characteristics between native and introduced mangroves 32,48 . For example, the introduced mangrove could accelerate nutrient cycling with higher fine root turnover and decomposition rates, leading to fast growth rates, low carbon storage capacity, and decreased nutrient content in the sediment 32,48 .…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Several studies also reported that coastal ecosystems vegetated with different mangrove species showed substantial variations in sediment properties, including pH, salinity, TC, and TN 32,47 . In this study, we observed different nutrient statuses (TC, TN, ammonium, and sulfate) and environmental conditions (pH and salinity) between native and introduced mangrove rhizospheres, which might be influenced by plant characteristics between native and introduced mangroves 32,48 . For example, the introduced mangrove could accelerate nutrient cycling with higher fine root turnover and decomposition rates, leading to fast growth rates, low carbon storage capacity, and decreased nutrient content in the sediment 32,48 .…”
Section: Discussionmentioning
confidence: 72%
“…In this study, we observed different nutrient statuses (TC, TN, ammonium, and sulfate) and environmental conditions (pH and salinity) between native and introduced mangrove rhizospheres, which might be influenced by plant characteristics between native and introduced mangroves 32,48 . For example, the introduced mangrove could accelerate nutrient cycling with higher fine root turnover and decomposition rates, leading to fast growth rates, low carbon storage capacity, and decreased nutrient content in the sediment 32,48 . Root exudates also showed direct impacts on rhizosphere properties (e.g., N and P) and microbial communities 35,46,49 .…”
Section: Discussionmentioning
confidence: 78%
“…However, microbial necromass C and C content are not the only reason for determining C sequestration. Although the individual biomass of exotic S. alterniflora and S. sonnertia was higher than that of native species, they showed lower soil C stock and C sequestration potential under similar environmental conditions, which may be due to the fine root turnover rates, fine root biomass and C accumulation rates (Feng et al, 2017; He et al, 2018, 2020, 2021; Yu, Feng, et al, 2020). For example, fine roots could play an important role in C sequestration in mangrove ecosystems, and the C stock was positively correlated with live fine root biomass and fine root necromass (He et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…coastal ecosystem, functional potential, metagenome sequencing, metagenome-assembled genome, microbial necromass carbon alien plants with high adaptability and growth rates are considered as pioneer species to improve degraded coastal habitats, but they have also caused a series of ecological and environmental risks, such as reduction of local biodiversity, decrease of C sequestration and increase of CH 4 emissions (He et al, 2018;Ren et al, 2008;Yu, Yang, et al, 2020). Most previous studies of soil C sequestration were mainly focused on the contribution of plant tissues (He et al, 2018(He et al, , 2021Zhu et al, 2020). For example, the introduced mangrove S. apetala was found to have higher fine root turnover rates but lower C sequestration compared to their native counterparts (He et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation